(Extraction of Blak Cincau Gel Forming Compound and Its Gelatinization Characteristics) - Dhiah Nuraini; Paulus Sunarto; Lucyana - (Balai Besar Industri Agro, 2000)
A study to extract and isolate gel forming compound (GFC)of black cincau had been conducted successfully using soda ash and alcohol as extracting and isolating agent. the result showed that the yield of GFC will increase with the increase of soda ash, and so will the Ph value of black cincau gel. the sensory test result showed that the highest acceptance score of black cincau gel was obtained from the extrtact using 5% soda ash. observation on gelatinization characteristics of black cincau showed that the addition of GFC will produce changes on amylogram pattern of tapioca, i.e. the increase of consitency with the increase of GFC addition. The amylogram also showed that black cincau GFC has tw fractions which interacted with strach